Role of Judiciary on Right to Privacy - Jha, Barsha Kumar (Sambahak: Human Rights Journal, 2024)
Privacy is one of the most valued human rights in the present context. It is crucial for the fullest development of the physical and mental growth of human beings. Judiciary is very effective to protect and promote Right to Privacy in a country through judicial activism or public interest litigation, the role of non-governmental organizations (NGOs) is also important in Nepal. This context requires the examination of existing judicial regime of Nepal to identify whether it adequately protects citizens’ rights to privacy. This paper aims at disclosure of this aspect of judicial interventions. The findings will enlighten all stakeholders to understand the existing legal framework for privacy in Nepal. It will further facilitate them to map and design their future policies and strategies encompassing privacy. It evaluates the role of judiciary in protecting, promoting and reinforcing the right to privacy with a descriptive and qualitative method of inquiry.